2020
DOI: 10.1007/s13165-020-00328-w
|View full text |Cite
|
Sign up to set email alerts
|

Dual-purpose production of eggs and meat—part 2: hens of crosses between layer and meat breeds show moderate laying performance but choose feed with less protein than a layer hybrid, indicating the potential to reduce protein in diets

Abstract: The use of modern chicken genotypes with high egg or meat performance results in the ethically unacceptable practice of culling day-old male layer chicks because of their inefficient fattening performance. Dual-purpose genotypes with a balanced performance profile for eggs and meat are one option to avoid this practice. In this study, the performance of four crosses of a layer breed (White Rock or New Hampshire) and the meat breed Bresse Gauloise, purebred Bresse Gauloise and the layer hybrid Lohmann Sandy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Foot pad lesions were not found at the end of the rearing period in either strain, but were present at the end of the observation period. This is in accordance with Baldinger and Bussemas (2021b) who found no foot pad lesions during rearing but found lesions at the end of the laying period in all strains. In our study, LT hens showed fewer lesions in comparison to the LD hens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Foot pad lesions were not found at the end of the rearing period in either strain, but were present at the end of the observation period. This is in accordance with Baldinger and Bussemas (2021b) who found no foot pad lesions during rearing but found lesions at the end of the laying period in all strains. In our study, LT hens showed fewer lesions in comparison to the LD hens.…”
Section: Discussionsupporting
confidence: 93%
“…In Germany killing day-old chicks is forbidden since January 2022 ( TierSchG, 2021 ) and in France it is also forbidden from 2022 onward but with a transitional period until December 2022 ( Ministère de, 2021 ). Beside in-ovo sex determination (e.g., Krautwald-Junghanns et al, 2017 ) and rearing of male chickens ( Koenig et al, 2012 ), a further possibility is to keep dual-purpose chicken breeds ( Mueller et al, 2020 ) in which both sexes are reared: The males for meat and the females for egg production, with both having moderate performance compared to strains selected either for egg or meat production ( Icken & Schmutz, 2013 ; Baldinger and Bussemas, 2021a , b ). The dual-purpose strain is a hybrid, with a crossing between layer and broiler strains.…”
Section: Introductionmentioning
confidence: 99%
“…A few years ago, birds from the French indigenous breed Bresse Gauloise were imported and started a new line BB that is now a part of the gene pool in the country. Research show that crossing Bresse with egg laying lines could result in good dual-purpose crosses, since Bresse Gauloise itself has a laying performance of 250 eggs and the live weight of the males could reach up to 3.0-3.6 kg (Baldinger and Bussemas, 2021b). Previous experiments with BB line showed that the birds have poorer vision compared to the rest of lines selected for industrial conditions and low light intensity.…”
Section: Introductionmentioning
confidence: 99%
“…While a broiler is usually fattened for 34 days to reach a slaughter weight of 2.1 kg (DLG, 2021), a DPB requires twice the amount of time (if not longer, depending on the particular breed) to reach a similar weight (Nolte et al, 2020b;Tiemann et al, 2020). Similarly, conventional laying hens lay around 310-330 eggs annually (DLG et al, 2020), while the laying performance of DPBs is 20-40% lower (Baldinger and Bussemas, 2021;Nolte et al, 2020a;Schultz, 2012). Although the production performance of DPBs is lower than that of conventional lines, their performance is usually better than native breeds or laying brothers (Lambertz et al, 2018;.…”
Section: Dual-purpose Chicken Breedsmentioning
confidence: 99%
“…As the main concern regarding dual-purpose breeds is their lower profitability due to their lower production performance, most literature regarding DPBs focuses on measuring fattening or carcass (Baldinger and Bussemas, 2021a;Lambertz et al, 2018;Tiemann et al, 2020) and laying (Baldinger and Bussemas, 2021b;Hammershøj et al, 2021; performance. However, animal performance is not the only important aspect of DPBs as it is imperative that the meat quality of the alternative breeds can meet that of modern broilers.…”
Section: Intrinsic Product Attributesmentioning
confidence: 99%